(untitled) (Global Journal of Science Frontier Research, 2012)
Differential subordination and superordination results are obtained for analytic functions in the open unit disk which are associated with Cho-Kwon-Srivastava operator. These results are obtained by investigating appropriate classes of admissible functions. Some of the result established in this paper would provide extensions of those given in earlier works.